ChemInform Abstract: Mild and Soft Catalyzed Trifluoromethylthiolation of Boronic Acids: The Crucial Role of Water. Issue 7 (January 2016) - Glenadel, Quentin; Alazet, Sebastien; Tlili, Anis; Billard, Thierry
Abstract: The reaction tolerates aryl, hetaryl, and alkenyl substituents endowed with a diverse range of functional groups.